Repeated batch fermentation of immobilized E. coli expressing Vitreoscilla hemoglobin for long-term use. Issue 5 (3rd September 2017) - Sar, Taner; Seker, Gamze; Erman, Ayse Gokce; Stark, Benjamin C.; Yesilcimen Akbas, Meltem
ABSTRACT: This study describes an efficient and reusable process for ethanol production from medium containing whey powder, using alginate immobilized ethanologenic E. coli strains either expressing (TS3) or not expressing (FBR5) Vitreoscilla hemoglobin. Reuseabilities of the FBR5 and TS3 strains were investigated regarding their ethanol production capacities over the course of 15 successive 96-h batch fermentations. The ethanol production was fairly stable over the entire duration of the experiment, with strain TS3 maintaining a substantial advantage over strain FBR5. Storage of both strains in 2 different solutions for up to 60 d resulted in only a modest loss of ethanol production, with strain TS3 consistently outperforming strain FBR5 by a substantial amount. Strains stored for 15 or 30 d maintained their abilities to produce ethanol without dimunition over the course of 8 successive batch fermentations; again strain TS3 maintained a substantial advantage over strain FBR5 throughout the entire experiment. Thus, immobilization is a useful strategy to maintain the advantage in ethanol productivity afforded by expression of Vitreoscilla hemoglobin over long periods of time and large numbers of repeated batch fermentations, including, as in this case, using media with food processing wastes as the carbon source.